Beam steering exploration for LiDAR - Ji, Yuequn (Nanyang Technological University, 2023)
Silicon photonic integrated circuits (PICs) are a type of integrated circuit (IC) that combines electronic and photonic components on a silicon substrate. Silicon photonic integrated circuits offer several advantages over traditional electronic circuits and other types of photonic devices, making them an ideal solution for a wide range of applications in various fields in the future. LiDAR (Light Detection and Ranging) is a remote sensing technology that uses light in the form of a laser to measure distances and create highly accurate 3D models of objects and environments. OPA can be used as a component within a LiDAR system to help steer the laser beam and control its direction. There are generally two types of mechanisms for beam steering in current LiDAR architectures: mechanical and non-mechanical. Optical phased arrays utilizing silicon photonics have emerged as a promising solution for solid-state LiDAR with advantages such as low cost, high speed, and robustness, while maintaining a compact footprint despite large optical apertures. The crucial factor in achieving beam steering is the control of phase differences among the beams. The one is changing the refractive index of the propagating medium, like TO effect and EO effect. Another way to categorize beam steering mechanisms in existing LiDAR architectures is based on the wavelength of the emitted laser beam. This article takes this method. In this paper, the steering angle range of 16-antennas phased array is obtained by optimizing the structural data of a single antenna. Compared with other literatures, the methods to improve the angle range and resolution are found. This paper uses several software for analysis, like FDTD, INTERCONNECT, and MATLAB.